MTP Arthrodesis: Outcomes of Crossroads Dynaforce and Stryker Locking Plate. Issue 1 (January 2022) - Andrews, Nicholas A.; Halstrom, Jared R.; Ray, Jessyca; Fellows, Kenneth J.; Harrelson, Whitt; Dib, Aseel G.; Agarwal, Abhinav; Elattar, Osama M.; Shah, Ashish
Category: Ankle; Midfoot/Forefoot Introduction/Purpose: Metatarsophalangeal (MTP) joint arthrodesis is commonly performed for end-stage hallux rigidus with largely satisfactory results. While current literature demonstrates union rates in the low 90's, there is still room for evolution of techniques and fixation constructs. The new Crossroads Dynaforce plate provides area for direct integration of a compression staple into the dorsal locking plate construct. The purpose of this present study was to compare outcomes of this new plating system to a standard dorsal locking plate from Stryker. Methods: Patients undergoing primary MTP arthrodesis from 2010-2020 were identified. Patients receiving Crossroads Dynaforce plates (23 patients) and Stryker Dorsal locking plates (21) for Hallux Rigidus were selected. Radiographic follow-up of >12 weeks and no ongoing ipsilateral infection were required for inclusion. Medical records were examined for patient characteristics, operative variables, and complications. PROMIS physical function, pain interference, and depression domains were collected postoperatively in addition to Foot Function Index (FFI). Results: The median age was 57.0 (IQR 16.0) with the average BMI of 30.4 (SD 11.2). No patient comorbidities or demographics were significantly different between Stryker and Crossroads groups. Importantly, the preoperative hallux valgus and intermetatarsal angles did not vary between groups. The use of an interfragmentary screw was significantly higher in the Stryker cohort 20/21 (95%) compared to 16/23 (70%) The rate of wound dehiscence, deep infection, and reoperation did not vary between groups. The nonunion rate did not differ between groups and was 3/21 (14.3%) in the stryker cohort compared to 1/23 (4.3%) in the Crossroads group. Patient reported outcomes measures did not differ between groups and were completed at an average of 2.2 years postoperatively (SD 1.9). Conclusion: The Crossroads Dynaforce plate provides comparable outcomes to a legacy dorsal locking plate from Stryker in hallux rigidus. In addition to clinical outcomes, patients report similar levels of function at intermediate term follow up.